Urinary incontinence in US adults aged ≥55 years with type 2 diabetes and indications for SGLT2is: NHANES 2013–2020 - Sei J Lee; Eva Raphael; Kathryn E Callahan; Kasia J Lipska; Alexandra K Lee (BMJ Open Diabetes Research & Care)
Objective Sodium-glucose cotransporter-2 inhibitors (SGLT2is) are recommended as first-line cardiorenal protective therapy in type 2 diabetes. Because SGLT2is cause glycosuria and increase urine volume, they may exacerbate incontinence symptoms among patients with pre-existing urinary incontinence. Our objective was to determine how many adults meeting guideline indications for SGLT2i have frequent urinary incontinence.Research design and methods We conducted a cross-sectional analysis of National Health And Nutrition Examination Survey (NHANES) participants aged ≥55 with type 2 diabetes in 2013–2020. We determined whether participants met American Diabetes Association guideline indications for an SGLT2i due to heart failure or chronic kidney disease, or due to atherosclerotic cardiovascular disease or high cardiovascular risk (for the latter two cardiovascular indications, GLP-1RAs are guideline-recommended alternative medications). Frequent urinary incontinence was defined by self-report of leaking urine daily/nightly or a few times per week.Results There were 1726 NHANES participants aged ≥55 with type 2 diabetes, representing 16.0 million US adults; 19.6% (95% CI 17.3% to 22.2%) (3.1 million) met indications for an SGLT2i specifically and 50.9% (95% CI 47.2% to 54.7%) (8.2 million) met indications for either an SGLT2i or a GLP-1RA. Among those with indications for an SGLT2i specifically, 32.4% (95% CI 25.9% to 39.8%) had frequent urinary incontinence, representing 333 000 men and 685 000 women. Among those with indications for either an SGLT2i or GLP-1RA, 25.5% (95% CI 20.8% to 30.8%) had frequent urinary incontinence, representing 630 000 men and 1413 000 women.Conclusions Frequent urinary incontinence affects >15% of men and >40% of women aged ≥55 years with guideline indications for SGLT2i. Studies are needed to determine if incontinence increases risk of genital infections when initiating SGLT2is.